Atomic Scale Structure of (Ag,Cu)2ZnSnSe4 and Cu2Zn(Sn,Ge)Se4 Kesterite Thin Films - Ritter, Konrad; Gurieva, Galina; Eckner, Stefanie; Preiß, Cora; Ritzer, Maurizio; Hages, Charles J.; Welter, Edmund; Agrawal, Rakesh; Schorr, Susan; Schnohr, Claudia S. (Frontiers in Energy Research, 2021)
Kesterite based materials are being researched and developed as affordable, efficient and mechanically flexible absorber materials for thin film photovoltaics. Both (Ag,Cu)2ZnSnSe4 and Cu2Zn(Sn,Ge)Se4 based devices have shown great potential in overcoming some of the remaining challenges for further increasing the conversion efficiency of kesterite based solar cells. This study therefore investigates the long range crystallographic structure and the local atomic scale structure of technologically relevant thin films by means of grazing incidence X-ray diffraction and low temperature X-ray absorption spectroscopy. As expected, the unit cell dimensions change about an order of magnitude more than the element specific average bond lengths. In case of Cu2Zn(Sn,Ge)Se4, the thin film absorbers show a very similar behaviour as Cu2Zn(Sn,Ge)Se4 powder samples previously studied. Small amounts of residual S in the thin films were included in the analysis and the results imply a preferential formation of Sn-S bonds instead of Ge-S bonds. In (Ag,Cu)2ZnSnSe4, the dependence of the Ag-Se and Cu-Se bond lengths on Ag/(Ag+Cu) might indicate an energetic advantage in the formation of certain local configurations.